RETROFIT POMPA SENTRIFUGAL UNTUK MENINGKATKAN KAPASITAS DISTRIBUSI BAHAN BAKAR MINYAK - Muhammad Auzan Winandi, (2021)
Due to the expanded amount of fuel consumption of the consumers, Cilacap - Yogyakarta (CY) fuel distribution network intends to optimize and increase the distribution capacity for a larger fuel supply. Following this, an increase in the performance of the booster pump with multistage between bearing type centrifugal pump on the Cilacap - Yogyakarta (CY) III pipeline system is necessary to fulfill the operating system needs. In this study, the method used to increase the pump capacity is to control the rotation of the pump by changing the gearbox ratio. Based on the pump performance analysis, retrofit aimed to increase the pump capacity from 250 m3/h to 300 m3/h can be done by increasing the pump rotation from 3600 rpm to 4320 rpm. This increase in pump rotation also affects the pump head which increases from 920 meters to 1325 meters. The power required increased from 680 kW to 1.175 kW. The Pump's Net Positive Suction Head required increased from 8 meters to 11,5 meters, and the pump's efficiency also increased from 78,4% to 85,5%. The rising amount of the pump's efficiency is due to the increase of the hydraulic power ratio to Brake kilo Watts